Effect of chlorine atoms on binding between amide herbicides and soil enzymes: Molecular mechanism and structure-activity relationship - Chuanxi Yang; Xiaoning Wang; Jingyan Lin; Yongkun Wu; Ziheng Wan; Weiliang Wang (Environmental Chemistry and Ecotoxicology)
Amide herbicides (AHs) significantly disrupt biogeochemical cycling of soil elements, particularly carbon, through the inhibition of key soil enzymes (SEs) activities. This study explores interactions between seven typical AHs and two SEs through molecular docking, density functional theory (DFT) calculations, and biotoxicity assessment to elucidate molecular mechanisms and structure-activity relationships (SAR) of these interactions. The study identifies key mechanisms underlying AHs-induced inhibition of SEs, focusing on functional groups, frequently occurring amino acids, hydrogen bonds, hydrophobic interactions, and the binding areas (BA) of pretilachlor (404.48 Å2 for β-glucosidase A (BG)) and butachlor (325.17 Å2 for alkaline invertase (AKI)). The absolute binding energies (|BE|) of propanil (2.94 kJ/mol for BG and 2.93 kJ/mol for AKI) were the highest, highlighting a significant SAR. A strong negative correlation was observed between BA and |BE| (r = −0.891, P ≤ 0.01). The biotoxicity of propanil, as indicated by the LC50 for fathead minnow in 96 h (LC50-96h, mg/L), IGC50 for Tetrahymena pyriformis in 48 h (IGC50-48h, mg/L), and LC50 for Daphnia magna in 48 h (LC50-48h, mg/L), was strongest. This enhanced toxicity is likely attributed to its smaller molecular structure, reduced steric hindrance, and higher halogen content (chlorine atoms). Differences in bulk phase and surface charges distribution were mainly influenced by the position of the Cl group, the distance of the O from the ether group, the N from the peptide bond, hydrocarbon chain length, and regions of negative charge enrichment. Correlations between BA, |BE|, and molecular weight (MW) of AHs with BG showed a positive relationship (r = 0.973, P ≤ 0.001), as well as a positive correlation with density (r = 0.836, P ≤ 0.05). Conversely, negative correlations were observed between BA, |BE|, and density (r = −0.811, P ≤ 0.05), and MW (r = −0.982, P ≤ 0.001). Similar correlations were found for AHs and AKI with density (r = 0.836, P ≤ 0.05), and negative correlations with MW (r = −0.955, P ≤ 0.001 and r = −0.982, P ≤ 0.0001). These findings suggest that the physicochemical properties of AHs drive the observed interactions with SEs.